Variation of microwave dielectric properties in the glucose biosensor system - Jafari, Fariba; Khalid, Kaida; Hassan, Jumiah; Abbas, Zulkifly; Md Salim, Nora Salina (Taylor & Francis, 2015)
Glucose biosensor is generally based on the reaction between glucose and glucose oxidase, which produces gluconic acid and hydrogen peroxide. The gluconic acid is a conductive material, while hydrogen peroxide has polar molecules. This article examines the changes of dielectric properties due to the conductive loss below 2 GHz and dipole orientation of above that frequency of this reaction. The difference between the dielectric loss of glucose solution and the dielectric loss of glucose-enzyme reaction can be related to the glucose concentration in the samples, such as orange juice, black grape juice, sugarcane juice, and sapodilla juice. A good sensitivity to these differences due to the effect of ionic conductivity and dipole orientation was found at 1 and 16.44 GHz, respectively. The minimum detection limit of glucose concentration in the proposed technique was about 0.01 M (0.20 g/100 ml) with an optimum reaction ratio of about 1:1 between the enzyme solution and the glucose solution. This technique could benefit the future development of microwave biosensor by which both ionic conductivity and dipole effects can be considered simultaneously.